LembreMe: The Effectiveness of Affective Micro-Interactions in Mobile JITAI-Style Reminder Systems – A Crossover Experimental Study - Santana, Alan de O.; Silva, Yuri D. da; Paradeda, Raul B. (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2026: Anais do XVIII Simpósio Brasileiro de Computação Ubíqua e PervasivaDO - 10.5753/sbcup.2026.21878, 2026)
This paper presents LembreMe, a Progressive Web App (PWA) designed to support individuals with executive function difficulties through personalized, just-in-time reminders on mobile devices. A crossover experimental study (N = 10) was conducted to compare affective reminders, incorporating empathetic language, personalization, emojis, and text-to-speech, with neutral reminders based on standard text and default notification sounds. The evaluated metrics included adherence rate, time to action, snooze frequency, user satisfaction (Likert scale), usability (System Usability Scale — SUS), and affective state measured using the Positive and Negative Affect Schedule. The results indicate that affective micro-interactions significantly increased task adherence, reduced task initiation latency, decreased snooze usage, improved user satisfaction, increased perceived usability, and enhanced positive affect. These findings suggest that incorporating affective elements into mobile reminder systems may enhance user engagement and contribute to the design of more effective JITAI-style interventions for executive function support.